“Representamen, Object and Interpretant in Humanitarian and Justice of Free Palestine Movement Taglines in Israel Allied Countries” - Oktaviani, Dini; Rusmana, Dadan; Ardiansyah, Erlan Aditya (Linguistics and ELT Journal, 2025)
This research examines the function of taglines and the semiotic structure of taglines used in the Free Palestine movement. The research examines the issue of how these taglines function as communicative tools and struggle tools, shaping meaning through semiotic mechanisms. Despite their widespread use on digital platforms, academic exploration of the communicative role and semiotic dimensions of these taglines is rare. Using a qualitative descriptive approach, this study applied semiotic theory, specifically using Charles Sanders Peirce's triadic model to analyze the selected taglines. The results of this study reveal several types of taglines, including descriptive, specific, superlative, imperative, provocative, each of which has a function as a form of support, expressing solidarity and challenging the dominant narrative. This research also identifies a semiotic structure consisting of Representamen (tagline as a sign), object (socio-political issue) and interpretant (ideological meaning constructed by the audience). This research concludes that the tagline in the Free Palestine Movement does not only convey linguistic expression but is a powerful semiotic instrument to provide resistance and mobilize public sentiment.